2003
DOI: 10.1080/10584580390259065
|View full text |Cite
|
Sign up to set email alerts
|

Screen Printed PZT Thick Films Using Composite Film Technology

Abstract: A spin coating composite sol gel technique for producing lead zirconate titanate (PZT) thick films has been modified for use with screen printing techniques. The resulting screen printing technique can be used to produce 10 µm thick films in a single print. The resultant films are porous but the density can be increased through the use of repeated sol infiltration/pyrolysis treatments to yield a high density film. When fired at 710• C the composite screen printed films have dielectric and piezoelectric propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…This is thicker than the currently possible with thin-film, solgel, piezoceramics which are limited to a maximum of about 10 mm thick due to internal stresses that build up during processing. 23 This is also thinner than commercially available bulk ceramics, which are a minimum of about 125 mm thick due to processing limitations. This size range allows the potential to embed piezoceramic transducers completely within typical adhesive layers without affecting the thickness, enabling embedding screen-printed piezoceramics into bonded and laminated structures.…”
Section: Materials Functionalizationmentioning
confidence: 99%
“…This is thicker than the currently possible with thin-film, solgel, piezoceramics which are limited to a maximum of about 10 mm thick due to internal stresses that build up during processing. 23 This is also thinner than commercially available bulk ceramics, which are a minimum of about 125 mm thick due to processing limitations. This size range allows the potential to embed piezoceramic transducers completely within typical adhesive layers without affecting the thickness, enabling embedding screen-printed piezoceramics into bonded and laminated structures.…”
Section: Materials Functionalizationmentioning
confidence: 99%
“…These films can be made by the technologies of jet printing [16,17], screen printing [18,19], tape casting [20,21], dipping [22,23], hydrothermal method [24,25], etc. Here an alternative sol-gel spray technique is used [14,15,26].…”
Section: Fabrication and Characterizationmentioning
confidence: 99%
“…Screen printing has been developed as a means of mass producing small-scale piezoceramic transducers, spanning thicknesses, and enabling geometries that cannot be achieved by other fabrication methods. Thin film fabrication methods like sol-gel and sputter coating are limited to thicknesses smaller than about 10 mm due to internal stresses that build up during fabrication (Dorey et al, 2003;Omori et al, 2001). Bulk ceramics are limited to thicknesses greater than about 100 mm and basic geometries due to machining and handling capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…This unique trait of porous piezoceramics is used in the hydrophone field where it is advantageous, but it is detrimental to the functionality of traditional parallel plate piezoelectric transducers in many applications, like piezoelectric wafer active sensors (PWAS) in SHM. Previous efforts to overcome this issue have focused on reducing the void fraction through sol-infusion or introduction of fillers (Dorey et al, 2003) and demonstrated limited success.…”
Section: Introductionmentioning
confidence: 99%